Appendicitis Associated With Clozapine: Analyses Based on a Spontaneous Reporting System Database in Japan. Issue 3 (30th May 2023) - Misawa, Fuminari; Nakajima, Nozomi; Fujii, Yasuo; Takeuchi, Hiroyoshi
Abstract: Background: An association between appendicitis and clozapine has recently been reported; however, few studies other than case reports have investigated this association. Therefore, we aimed to investigate the association between appendicitis and clozapine, using a large spontaneous reporting database in Japan. Methods: Japanese Adverse Drug Event Report data were used in this study, and patients who had received clozapine or nonclozapine second-generation antipsychotics (NC-SGAs) available in Japan were included. To compare the reporting frequency of appendicitis associated with clozapine and NC-SGAs, we calculated the adjusted reporting odds ratio using logistic regression models, adjusting for age group, sex, and anticholinergic use. We conducted a time-to-event analysis to examine the time to onset of appendicitis associated with clozapine. Results: In total, 8921 patients were included in this study, of whom 85 (1.0%) had appendicitis. Of these, 83 patients had received clozapine. Appendicitis was significantly more frequently reported with clozapine than with NC-SGAs. Time-to-event analysis showed that the risk of developing appendicitis associated with clozapine increased over time. Conclusions: Clozapine was associated with a higher risk of appendicitis than NC-SGAs, which increased with time. These findings suggest that clinicians need to pay greater attention to the risk of developing appendicitis during clozapine treatment.